Photosensitive AlGaAs / GaAs Structures Grown by Molecular Beam Epitaxy - M.A. Bazalevsky; G.I. Koltsov; S.I. Didenko; S.Yu. Yurchuk; S.A. Legotin; O.I. Rabinovich; V.N. Murashev; I.P. Kazakov (Журнал нано- та електронної фізики)
AlGaAs / GaAs photosensitive structures were grown by molecular beam epitaxy and photodetector devices were fabricated. The structures were characterized by reflection high-energy electron diffraction (RHEED), reflectance anisotropy spectroscopy (RAS) and atomic force microscopy (AFM). Spectral characteristics of p-i-n structures were calculated. It is shown that obtained structures have atomically smooth surface and abrupt heterointerfaces. Room-temperature I-V measurements of fabricated photodetectors showed low dark current Id = 3.38 nA at reverse bias Urev = 5 V.